(3cJGH aj GdCOhjI GdeaQOI hGdCZPjIs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3Chd hCMb eG GHJOF Hg GdcJGH GdJYXje dGSe Gddg JYGdi GYde abW Gddg JYGdi Cfg deG cGfJ GdCOhjI hGdCZPjI eGOI dMaX UMI GdCfSGf s
(3BNQgG (B:s
(3agPg gi GdbhGfjf GdcdjI GdJi jLH Cf jYQagG GdWHjH ef CehQ GdCOhjI GdeaQOI , hGddg SHMGfg hJYGdi Gdehab ddUhGH hfSGdg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQg eY Jbhje GdCHOGf (B_ (3fSNI UfYGA Qbe (B" 413"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B197 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdZQHjI HUfGYGA (B((3WH (B10) s
Keywords: (3GdWHs